Pengaruh Harga, Merek, dan Fitur terhadap Keputusan Pembelian Mobil Wuling Type Confero PT. Maju Global Motors Di Kota Jambi - Mela Rahma Sari (Universitas Batanghari Jambi, 2022)
The purpose of this study is a follows: 1) to find out the price, brand, features, and purchasing decisions of Wuling Type Confero cars in Jambi City, and 2) To analyze the influence of prices, brands, and features on purchasing decisions on Wuling Type Confero car consumers in Jambi City simultaneously . The analytical method used is quantitative data analysis method, namely the analysis used to test the relationship or influence of the independent variable (X) and the dependent variable (Y). The analytical tools in this study are simple linear regression analysis, hypothesis testing and the coefficient of determination (R2). Based on the criteria, the samples taken were 32 Civil Servants at the Jambi City Education Office. From the results of simple linear regression analysis, it is concluded that the regression equation Y = -0,027 + 0.088 X1 + 0.779X2 + 0.154X3, its mean that constant value of -0,027 means that if the lifestyle variable (X) is 0. then the Buying Decision variable (Y) is -0,027. if price (X1), brand (X2), and features (X3) are all equal to zero. Therefore, it is clear that without prices, brands and features, consumers will be less likely to make purchase decisions. The conclusion is, 1) Consumer perception of Wuling car prices at PT. Maju Global Motors Jambi z City categorized as high with an average score of 279.9, the perception of the Wuling car brand at the PT Store. Maju Global Motors Jambi z City categorized as high with an average score of 299.4, the perception of Wuling car features at the PT Store. Maju Global Motors Kota Jambi is categorized as high with an average score of 275.3, while purchasing decisions are categorized as high with an average score of 299.9. 2) Price, brand, and features have a significant effect on Wuling's car purchase decision at the PT. Advancing Global Motors Jambi City simultaneously (together), and 3) partially, Price (X 1), Brand (X 2) and Features (X3) have a significant effect on Wuling's Car Purchase Decision at the PT Store. Maju Global Motors Jambi City.